Influencia de las condiciones ambientales en la concentración de compuestos activos de los aceites esenciales de eucalipto Eucalyptus globulus L., menta Mentha piperita L. y jengibre Zingiber officinale extraídos de cultivos de diferentes zonas de Ecuador - Almeida Sánchez, Daniela Angélica (2024)
The objective of this titration work was to analzed the influence of environmental conditions on the concentration if active compounds in essential oils of eucalytus, peppermint and ginger extracted from crops in different áreas of Ecuador. Descriptive research was carried out, with an explorator level, using a bibliografic review method. The study population consisted of eucalytus crops in the áreas of Bolivar and Azuay, mint in the áreas of Loa and Napo, and ginger in the areas of Pichincha and El Oro. A significant variation in the production and quility of essential oils was observed in different áreas of the country, highlighting the importance of considering these conditions to maximize the production of desirable active compounds. The results obtained from this research were explicit in denothing that temperatura, altitudinal conditions and relative alteration in these compounds, and as such win the quality of these products in ordder to highlight the conditions suitable for their greater production and medicinal efficacy. Finally, it was concluded that climatic conditions are key factors that significantly alter the composition of active principles in the essential oils of each species in the different study sites. Therefore, these studies allow to promote the optimization of agroindustrial proccess, since it gives thew extrac location of were the highest and lowest number of compounds are found according to the essential oil to be obtained.